Analisys of particles transportation applied to a ship's ballast system by using fastcam recorded images. Issue 1 (July 2021) - Amoresano, A.; Iodice, P.; Langella, G.; Mocerino, L.; Quaranta, F.
Abstract: High-performance imaging techniques represent the present of academic and industrial research. The use of these technologies in the maritime sector sees different applications in different phases of the life of a ship: photogrammetry in the design phase and the use of Lidar sensors to measure emissions are just a few examples. The novelty of this study is the application of these acquisition techniques to ship ballast systems. The new ballast water management regulations aimed at limiting the alteration of the marine ecosystem has overturned the canonical use of the ballast systems. In recent years, studies have shown how the spillage of ballast water has generated the proliferation of invasive species in seas all over the world. For this reason, the IMO has tried to regulate these operations. In this work, transportation phenomena of sediments through the duct, suctioned by a pump have been analysed. The inspected duct has been exposed to a CMOS MINI FASTCAM AX100. This camera was used to acquire images that allow studying the behaviour of the particles. With the use of a Matlab toolbox, a post processing of the images has been realized in order to estimate the speed and accelerations of the particles.